Reliability of Health-Related Physical Fitness Tests among Colombian Children and Adolescents: The FUPRECOL Study - Ramírez-Vélez, Robinson; Rodrigues-Bezerra, Diogo; Correa-Bautista, Jorge Enrique; Izquierdo, Mikel; Lobelo, Felipe (PloS one, 2015)
Substantial evidence indicates that youth physical fitness levels are an important marker of lifestyle and cardio-metabolic health profiles and predict future risk of chronic diseases. The reliability physical fitness tests have not been explored in Latino-American youth population. This study's aim was to examine the reliability of health-related physical fitness tests that were used in the Colombian health promotion "Fuprecol study". Participants were 229 Colombian youth (boys n = 124 and girls n = 105) aged 9 to 17.9 years old. Five components of health-related physical fitness were measured: 1) morphological component: height, weight, body mass index (BMI), waist circumference, triceps skinfold, subscapular skinfold, and body fat (%) via impedance; 2) musculoskeletal component: handgrip and standing long jump test; 3) motor component: speed/agility test (4x10 m shuttle run); 4) flexibility component (hamstring and lumbar extensibility, sit-and-reach test); 5) cardiorespiratory component: 20-meter shuttle-run test (SRT) to estimate maximal oxygen consumption. The tests were performed two times, 1 week apart on the same day of the week, except for the SRT which was performed only once. Intra-observer technical errors of measurement (TEMs) and inter-rater (reliability) were assessed in the morphological component. Reliability for the Musculoskeletal, motor and cardiorespiratory fitness components was examined using Bland-Altman tests. For the morphological component, TEMs were small and reliability was greater than 95% of all cases. For the musculoskeletal, motor, flexibility and cardiorespiratory components, we found adequate reliability patterns in terms of systematic errors (bias) and random error (95% limits of agreement). When the fitness assessments were performed twice, the systematic error was nearly 0 for all tests, except for the sit and reach (mean difference: -1.03% [95% CI = -4.35% to -2.28%]. The results from this study indicate that the "Fuprecol study" health-related physical fitness battery, administered by physical education teachers, was reliable for measuring health-related components of fitness in children and adolescents aged 9-17.9 years old in a school setting in Colombia.